홍도고들빼기의 형태 다양성 및 잡종 기원의 분자 증거 - 장영종; Young-jong Jang; 박범균; Boem Kyun Park; 손동찬; Dong Chan Son; 최병희; Byoung-hee Choi (Sigmul bunryu hag-hoeji = Korean journal of plant taxonomy, 2022)
홍도고들빼기는 이전 연구에서 형태적 특성과 지리적 분포를 바탕으로 이고들빼기와 갯고들빼기의 잡종인 Crepidiastrum ×muratagenii로 제안된 바 있지만, 이에 대한 분자적 증거를 제시하지 못하였다. 본 연구는 홍도고들빼기의 잡종 기원을 밝히기 위하여 홍도고들빼기와 그 근연종의 추가적인 형태적 형질을 관찰하였으며, 핵리보솜 internal transcribed spacer (ITS) 구간과 엽록체 구간(trnT-L, trnL-F, rpl16 intron, rps16 intron)의 염기서열을 비교·분석하였다. 형태적 특성을 검토한 결과, 잡종형은 생육형, 줄기잎, 외총포편, 수과의 특성을 바탕으로 세 가지 유형으로 구분되었다. 분자 분석 결과, Type 1형과 Type 2형은 ITS 구간의 종식별부위에서 혼성화가 관찰되었으며, 엽록체 구간에서는 Type 1형은 이고들빼기, Type 2형은 갯고들빼기 서열이 각각 관찰되었다. Type 3형은 ITS와 엽록체 구간 모두 이고들빼기와 동일한 서열을 보였다. Type 1형과 Type 2형은 이고들빼기와 갯고들빼기의 형태가 혼합되어 나타날 뿐 아니라, 분자 분석에서도 절영풀이 아닌, 갯고들빼기와 이고들빼기의 종식별부위에서 혼성화가 관찰되어 이고들빼기와 갯고들빼기의 잡종임을 지지하였다. 그러나 Type 3형은 형태적 형질이 다른 잡종형과 유사하나 외총포편이 이고들빼기와 유사한 점에서 구분되며, 분자 분석에서도 이고들빼기 서열과 동일하여, 이고들빼기의 생태변이로 판단되었다. The plant “Hong-do-go-deul-ppae-gi” has been considered as Crepidiastrum × muratagenii, a hybrid between C. denticulatum and C. lanceolatum, based on its morphological traits and geographical distribution. To reveal the hybrid origin of Hong-do-go-deul-ppae-gi, we examined additional morphological traits of this plant and its putative parents (C. denticulatum, C. lanceolatum, C. platyphyllum) and analyzed one nuclear ribosomal internal transcribed spacer (ITS) region and four chloroplast regions (trnT-L, trnL-F, rpl16 intron, and rps16 intron). As a result of examining the morphological traits, putative hybrid individuals were classified into three types based on the habit, cauline leaf, outer phyllary, and achene beak traits. A molecular analysis found that the ITS sequences of Type 1 and Type 2 individuals showed additive species-specific sites of C. denticulatum and C. lanceolatum. Plastid sequences of Type 1 and Type 2 individuals showed C. denticulatum and C. lanceolatum sequences, respectively. However, Type 3 individuals had ITS and plastid sequences corresponding to C. denticulatum. Accordingly, Type 1 and Type 2 individuals not only share morphological traits with C. denticulatum and C. lanceolatum but also show additive species-specific sites for C. denticulatum and C. lanceolatum, and not C. platyphyllum, supporting its origin as a hybrid between C. denticulatum and C. lanceolatum. Type 3 had morphological traits similar to other hybrid types but was distinguished with respect to outer phyllaries and demonstrated some resemblance to C. denticulatum. In a molecular analysis, Type 3 was found to be identical with regard to the sequence of C. denticulatum and was judged to be an ecological variation of C. denticulatum.